Hypertensive crisis in patients with obstructive sleep apnea-induced hypertension - Sittichai Khamsai; Apichart Chootrakool; Panita Limpawattana; Jarin Chindaprasirt; Wattana Sukeepaisarnjaroen; Verajit Chotmongkol; Songkwan Silaruks; Vichai Senthong; Yuwares Sittichanbuncha; Bundit Sawunyavisuth; Kittisak Sawanyawisuth (BMC Cardiovascular Disorders, 2021)
Abstract Background Hypertensive crisis is an urgent/emergency condition. Although obstructive sleep apnea (OSA) in resistant hypertension has been thoroughly examined, information regarding the risk factors and prevalence of hypertensive crisis in co-existing OSA and hypertension is limited. This study thus aimed to determine prevalence of and risk factors for hypertensive crisis in patients with hypertension caused by OSA. Methods The inclusion criteria were age of 18 years or over and diagnosis of co-existing OSA and hypertension. Those patients with other causes of secondary hypertension were excluded. Patients were categorized by occurrence of hypertensive crisis. Factors associated with hypertensive crisis were calculated using multivariate logistic regression analysis. Results There were 121 patients met the study criteria. Of those, 19 patients (15.70%) had history of hypertensive crisis. Those patients in hypertensive crisis group had significant higher systolic and diastolic blood pressure at regular follow-ups than those without hypertensive crisis patients (177 vs. 141 mmHg and 108 vs. 85 mmHg; p value < 0.001 for both factors). After adjusted for age, sex, and Mallampati classification, only systolic blood pressure was independently associated with hypertensive crisis with adjusted odds ratio (95% CI) of 1.046 (1.012, 1.080). Conclusions The prevalence of hypertensive crisis in co-existing OSA and hypertension was 15.70% and high systolic blood pressure or uncontrolled blood pressure associated with hypertensive crisis in patients with OSA-associated hypertension.